A caminho da institucionalização do modelo ISO 9000 no setor da construção civil do Espírito Santo - Romano, Bruno Dessaune (2004)
The subject of this thesis is the civil construction sector in the state of Espírito Santo, Brazil, with the primary focus on the ISO 9000 and PBQP-H certifications. The objective is to investigate the occurrence of an institutionalization process of the